Pengaruh Citra Merek Dan Persepsi Harga Terhadap Keputusan Pembelian Produk Mitsubisi Xpander Di Jakarta, Bogor,Depok,Bekasi, Tanggerang Dan Kabupaten Karawang - Alfaruq, Aldila Amirun; Ramadhan, Fajar (Peneliti.net, 2024)
This study aims to describe the influence of brand image and price perception on the Mitsubishi Xpander and determine the influence of correlation, partial and simultaneousness on the Mitsubishi Xpander purchasing decisions in Jakarta, Bogor, Depok, Tangerang, Bekasi, and Karawang Regency. This research method is a type of descriptive quantitative research. The study population was 260,803 with a sample size of 190 people calculated using the formula Hair et al. The results of the descriptive analysis research showed that brand image variables were considered agreeable, price perception variables and purchase decisions were considered very agreeable, while verification analysis showed that there was a correlation between brand image and price perception 49.7%, partial influence of brand image on purchasing decisions 31.4% and price perception on purchasing decisions 51.4%, simultaneous influence of brand image and price perception on purchasing decisions 52.2%. Mitsubishi Xpander company, Mitsubishi Motors, should pay attention to several dimensions that have weak values in measuring the variables of this study, namely the cultural dimension of brand image by approaching the community in getting new consumers, the dimension of affordability of product prices in price perception by making price adjustments or reducing production costs so that they can be reached by all groups, The dimension of brand choice in purchasing decisions by promoting products to be known by all circles.